2021
DOI: 10.1021/acsami.1c08484
|View full text |Cite
|
Sign up to set email alerts
|

Combining ReaxFF Simulations and Experiments to Evaluate the Structure–Property Characteristics of Polymeric Binders in Si-Based Li-Ion Batteries

Abstract: High energy capacity silicon (Si) anodes in Li-ion batteries incorporate polymeric binders to improve cycle life, which is otherwise limited by large volume and stress fluctuations during charging/discharging cycles. Several properties of the polymeric binder play a role in achieving optimal battery performance, including interfacial adhesion strength, mechanical elasticity, and lithium-ion conduction rate. In this work, we utilize atomistic simulations with the ReaxFF force field and complementary experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that weak interfacial adhesion between the active materials and the binders give rise to particle agglomeration. 52 Thus, the degree of the particle 3f). In contrast, the obvious agglomeration of active materials was observed in the SiO x / PGA (Figure 3g) and SiO x /CMC (Figure 3h) electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that weak interfacial adhesion between the active materials and the binders give rise to particle agglomeration. 52 Thus, the degree of the particle 3f). In contrast, the obvious agglomeration of active materials was observed in the SiO x / PGA (Figure 3g) and SiO x /CMC (Figure 3h) electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that weak interfacial adhesion between the active materials and the binders give rise to particle agglomeration . Thus, the degree of the particle agglomeration can predict the interfacial adhesion between SiO x particles and the binder.…”
Section: Resultsmentioning
confidence: 99%
“…The fabrication of Si/PPAN anodes employed a similar procedure that had been reported previously. Si microparticles (∼2 to 3 μm, Silgrain e-Si, Elkem) were mixed with polyacrylonitrile (PAN, M w ≈ 150,000, Sigma-Aldrich) at a 70:30 (% w/w) Si:PAN ratio, using N , N -dimethylformamide as the solvent (dimethylformamide (DMF), ≥99.9%, Sigma-Aldrich). The slurry was then spray-coated onto a copper current collector (MTI Corp.) utilizing an airbrush (Model G22, Master Airbrush).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…85 Besides, Senftle et al found that pyrolyzed polyacrylonitrile (PPAN) chains exhibit dense and highly ordered stacking behavior at the anode interface due to repeated pyridine structures, leading to stronger adhesion and higher Li + conductivity. 86 In a subsequent study, Huo et al reported a stretchable conductive glue (CG) binder formed by cross-linking of D-sorbitol and vinyl acetate−acrylic (VAA) onto PEDOT:PSS chains. This binder can be stretched up to 400% in volume without losing conductivity (Figure 11C).…”
Section: Improving the Mechanical Properties Of Conductive Bindersmentioning
confidence: 99%